2015
DOI: 10.1021/acs.jctc.5b00026
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling of Triton X Micelles: Force Field Parameters, Self-Assembly, and Partition Equilibria

Abstract: Nonionic surfactants of the Triton X-series find various applications in extraction processes and as solubilizing agents for the purification of membrane proteins. However, so far no optimized parameters are available to perform molecular simulations with a biomolecular force field. Therefore, we have determined the first optimized set of CHARMM parameters for the Triton X-series, enabling all-atom molecular dynamics (MD) simulations. In order to validate the new parameters, micellar sizes (aggregation numbers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 82 publications
3
33
0
Order By: Relevance
“…COSMOmic was recently optimized for charged solutes, with regards to the membrane dipole potential [181]. COSMOmic has proved its usefulness for the determination of membrane/water partition coefficients for different solutes [77,126,[179][180][181][182][183][184][185][186][187] and for micelle/water partition coefficients [183,[188][189][190][191]. It was also shown that the results of COSMOmic and MD simulations are comparable [126,182].…”
Section: Cosmomicmentioning
confidence: 99%
“…COSMOmic was recently optimized for charged solutes, with regards to the membrane dipole potential [181]. COSMOmic has proved its usefulness for the determination of membrane/water partition coefficients for different solutes [77,126,[179][180][181][182][183][184][185][186][187] and for micelle/water partition coefficients [183,[188][189][190][191]. It was also shown that the results of COSMOmic and MD simulations are comparable [126,182].…”
Section: Cosmomicmentioning
confidence: 99%
“…27 Very recently, an optimized set of CHARMM parameters for the Triton X-series, suitable for atomistic molecular dynamics (MD) simulations, has been 5 presented. 28 Although atomistic simulations provide very detailed models of surfactants, they are highly computationally expensive techniques for studying the assembling processes involving nanostructures occurring on the mesoscopic time and length scales. Indeed, the assembly process of surfactants can be obtained only in some cases from a random mixture of surfactants in aqueous solution within atomic resolution with reasonable simulation time.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, aggregates with ε = 0 correspond to a highly symmetrical shape with spherical geometry, while values different from zero indicate drifts to a more elliptical shape. 23,42,43 By monitoring the variation of ε over the simulation time, we conclude that the aggregate cannot be considered entirely spherical but resembling a spheroid (ε = 0.15-0.3). ε values correlate well with the variations of the radius of gyration (Rg) on the principal axes of the micelle [Fig.…”
Section: A Self-assembly and Micellizationmentioning
confidence: 97%
“…By assuming that the micelle adopts a spherical shape under high pressures, the Rg can be calculated as the Thus, the radius of the micelle, Rs, can be calculated from the relation to Rg according to 23,43 Rs = 5 3 Rg.…”
Section: B Pressure Effectsmentioning
confidence: 99%
See 1 more Smart Citation